Covid-19 mRNA vaccines: a new window opens in the field of immunology (Research, Society and Development, 2021)
Introduction: Messenger RNA (mRNA) technology is a platform that has been investigated for many years. The emergence of the Covid-19 pandemic forced scientists from all over the world to unite around the development of several vaccines, having bet on those that are considered conventional, that is, based on the virus itself, but inactivated, or on its fragments, cultivating them in the laboratory. Objective: To demonstrate the mechanism of action of mRNA vaccines against Covid-19. Methodology: This is a descriptive research of the integrative literature review type, which seeks evidence on mRNA vaccines against Covid-19. The search was conducted using PubMed, MEDLINE, Scielo, CDSR, Google Scholar, BVS and EBSCO databases, from 2015 to 2021. Results: The ANN approach is a very interesting and important fact, because these ANNs, identical to viral, are introduced into the cells of the human body's immune system, inducing them to produce parts of a protein that the virus also manufactures, called spike (S), easily identified through each of the tips that are already known in the Covid-19 virus images. Conclusion: This is just the beginning of a great technological revolution for the production of vaccines that may, in the future, fight several other viruses using this technology with different mRNA segments, providing the development of treatments for various diseases through the same principle of action.